The value of multiculturalism in Indonesian language textbooks as an internalization of inclusive education in the AI technology era - Sakinah Isna Firmani; Diah Rahma Cahya Agustyowati; Fathul Hidayati; Ruli Nur Safitri; Gail Ekici (BAHASTRA, 2026)
Multicultural education at the senior high school level plays a crucial role in fostering tolerant student characters, promoting respect for diversity, and creating inclusive learning environments. This study aimed to explore the multicultural values within Grade XI Indonesian language textbooks as a form of internalizing inclusive education in the era of artificial intelligence (AI) technology. Utilizing a descriptive qualitative method, this study analysed multicultural values as the research object, with Grade XI Indonesian language textbooks serving as the research subject. Data were gathered using the scrutinizing and note-taking techniques, while the data analysis process involved data collection, data reduction, data display, and conclusion drawing. The results revealed that the Grade XI Indonesian language textbooks incorporated several multicultural values, including justice, tolerance, equality, and democracy. These values were embedded across three dimensions—knowledge, skills, and attitudes—and were represented through reading texts, exercises, and student reflective activities. These findings confirm that Indonesian language textbooks serve as a strategic medium for internalizing inclusive education. In the AI era, these multicultural values can be implemented more effectively through personalized and inclusive learning. Ultimately, the integration of value-rich textbooks and AI technology supports the creation of an equitable, inclusive education system oriented toward the well-being of all students.